Parasitic Helminths eggs as bio-indicators for environment contamination of Al-Hwiez dam water, Jableh – Syria - Hasan, Bushra Mohammed; Dayoub, Amal Ibrahim (Journal of agricultural, environmental and veterinary sciences, 2022)
In order to reveal the suitability of Al-Hwiez Dam water in Jableh district for agricultural irrigation, we relied on the World Health Organization (WHO), which considered the eggs of intestinal roundworms as one of the bio-healthy indicators of sewage contamination with helminthes eggs.Water samples from the selected sites of the lake were collected from March to June 2021 with average 10L/weekly and transferred to the laboratory at the Higher Institution of Environmental Researches in Tishreen University to processed for parasitic analysis to determine the presence and concentration of helminth eggs and to determine their types and spread in the dam water based on specific reference methods. Results revealed that 24 out of 32 samples (75%) processed water samples from Al-Hwiez Dam water were contaminated with helminths eggs with enumeration 6.3 egg/liter which is above the WHO permissible limit, hence this water cannot be reuse in agricultural irrigation and human activities. According to the approved international classification standards, the morphological and taxonomic study of the recovered eggs showed that they belong to six types, namely: Ascaris sp. (31%), Hookworms (6%), Enterobius vermicularis (23%), Fasciola hepatica (6%), Taenia sp. (11%), and Toxocara cati (23%). The most prevalent eggs were Ascaris sp, Enterobius vermicularis and Taxocara respectively. Resulting, our study proved that the dam water is contaminated with sewage and agricultural waste where the recovered eggs was both human and animal origin; note that this study is the first locally in the field of parasitic contamination of Al-Hwiez Dam water.
Keywords: Parasitic Helminths eggs; Bio-indicators; Al-Hwiez dam; Syria